Comparative Susceptibility of Anaerobic Bacteria to Minocycline, Doxycycline, and Tetracycline - Chow, Anthony W. (1975)
The comparative susceptibility of 622 recent clinical isolates of anaerobic bacteria to minocycline, doxycycline, and tetracycline was determined by an agar-dilution technique. In addition to Bacteroides fragilis, a variety of other anaerobic bacteria was resistant to achievable blood concentrations of tetracycline (55% inhibited by 6.25 μg/ml) and doxycycline (58% inhibited by 2.5 μg/ml). In contrast, minocycline was significantly more active (P < 0.05) than both doxycycline and tetracycline, and 70% of strains were inhibited by achievable blood concentrations of this antibiotic (2.5 μg/ml). The enhanced activity of minocycline was particularly striking for Peptococcus asaccharolyticus, P. magnus, P. prevotii, Peptostreptococcus anaerobius, and Bacteroides melaninogenicus. Further evaluation of the clinical efficacy of minocycline against anaerobic infections is indicated.